Studying Laser Diode Dynamics with Optical Feedback from 20cm Free Space External Resonator - Hemed, Ayser A. H.; Mohammad, Adnan H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this experimental study, which was carried out in photonics laboratory at Strathclyde University, UK, dynamics of a multi-Quantum well semiconductor active medium laser, was studied. This is in order to study its emission stability and pulse shape development under the influence of strong optical feedback level with different deriving currents, in the free space transmission medium. An external stable resonator was constructed by inserting high reflectivity dielectric mirror outside the laser output, 20 cm apart from it, which is an extralarge external cavity. Controlling the reflected back optical power was done by using a nonpolarized (50:50) beam splitter. The external resonator supported by focusing (plano-convex) lens in order to make it stable. Laser translated from stable emission when it was solitary, to quasi-static, and low fluctuated, behaves, to be coherence collapse. This is due to the strong (50%) level of optical feedback.